Milho segunda safra 2012: análise do perfil nutricional na composição de dietas para frangos de corte - Giacomini, Camila Borba Santos (2015)
The aim was to determine the chemical composition of different corn and evaluate them in diets for broilers. Two experiments were conducted, one for the digestibility of diets with broilers from 1-21 days old in batteries, and other to evaluate the performance of broilers from 1 to 42 days of age. The thesis was divided in four chapters, the first was a bibliographic revision, the second and the third to describe the experiments and the fourth to discuss the nutritional value of corn and evaluate which corn was more efficient to feed broilers. In both experiments the treatments were seven diets, each diet with different corn lots (H-14, H-25, H-36, H-47, H-58, H-69 and H-70) from a grain genetics company harvested in second crop of 2012. Water and feed were ad libitum. The raw energy and the chemical composition (dry matter, crude protein, total aminogram, ether extract, starch, amylose, calcium, phosphorus, crude fiber and ash) were analyzed samples of ingredients and the diets. In the experiment I, 560 broilers were distributed Cobb 500, males, in a completely randomized design (CRD) with seven treatments and eight replicates of ten birds each. The chicks were housed in batteries. Excreta were collected to analysis of total nitrogen, ammoniacal nitrogen and phosphorus from 17th to 20th day of age of the birds. At 21 days of age were slaughtered eight birds per replicate, to collect the ileal content to be analyzed, and after calculate the digestibility of gross energy and all nutrients in the diet. In the second trial, were distributed in 2520 broiler Cobb 500, males with 1 day old, in CRD with seven treatments and eight replicates of 45 birds each. The chicks were housed in experimental boxes of 3.61m² compounds of drinker nipple system and a tubular feeder. The feeding program was divided into four phases: initial phase (1 to 21 days of age); growth 1 phase (22 to 28 days); growth 2 phase (29 to 35 days) and final phase (36 to 42 days). The parameters evaluated were: body weight, weight gain, feed intake in each experimental week and feed conversion by weight gain, livability and productive efficiency index in all period. At 42 days old, three birds per replicate were slaughtered pen to evaluate carcass characteristics and weight of liver and heart. In the third article was discussed the results of the chemical and energy corn composition, and the economic analysis by the average cost of diets and feed cost to produce one kg of chicken. The data were submitted to ANOVA and when the P<0.05, the means were compared by Tukey test (5%), using the SAS (2001) program. The ileal digestibility coefficients were statistically similar for each nutrient, and energy of diets. On average 1.09% phosphorus and 5.27% of total nitrogen was excreted by birds, with no significant difference between the corns used. However, the ammoniacal nitrogen had higher concentration in excreta of birds of H-25 and H-70 treatments than in birds of the H-14. In the performance study, there was no difference between treatments on feed intake, livability, breast weight, heart, liver and abdominal fat. The body weight and carcass weight were significantly higher in birds fed H-69 compared to birds fed H-25. The chemical composition of corn was similar to values found in literature to common corn, but the starch content and ether extract were higher than the values found in nutritional tables. The corn influenced in weight gain of birds (P=0.0099), in the cost of consumed diet (P=0.0027) and cost of production by weight gain (P=0.0001). All diets, with different maize studied in this experiment had similar nutrient digestibility weighted excretion of phosphorus and total nitrogen, and may be used in poultry from 1 to 21 days of age. The H-69 corn favored the better bird performance by presenting best productive efficiency index and lower feed conversion than birds of the H-25. This result can be explained by the correction of the diet, which was included in the diet increased oil content with H-69 corn. The H-58 corn was the most efficient in cost:gain, with effects possibly caused by better use of amylose by chickens.